Mosquito (Diptera: Culicidae) Bloodmeal Sources During a Period of West Nile Virus Transmission in Puerto Rico - BARRERA, ROBERTO (J Med Entomol, 2011)
Host bloodmeals of indigenous Caribbean mosquitoes have not been studied previously. We identified vertebrate DNA in 90 blood-engorged mosquitoes belonging to four genera (Aedes, Culex, Deinocerites, and Uranotaenia) and 12 species that were collected in Puerto Rico within a geographic and temporal focus of West Nile virus transmission in 2007. It was found that 62 (68.8%) bloodmeals were from reptiles, 18 (20.0%) from birds, and 10 (11.1%) from mammals. Only one bloodmeal of 18 derived from Culex (Culex) species was passerine, suggesting a preference for nonpasserine birds and other vertebrates (i.e., reptiles) among the candidate WNV vectors. We interpret the results with respect to vectorial capacity for West Nile virus, an emerging arbovirus throughout the Caribbean Basin.